THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE OF REPRODUCTIVE HEALTH AND PREMARITAL SEXUAL ATTITUDES IN STUDENTS AT SMK MUHAMMADIYAH 1 RANGKASBITUNG, LEBAK REGENCY IN 2023 - Darningsih, Ayu; Yuliani, Indah (HEARTY, 2025)
Background: Based on a preliminary study conducted at SMK Muhammadiyah 1 Rangkasbitung, Lebak Regency, it was found that 90% (18 out of 20) students had a spouse. Purpose: To determine the relationship between the level of reproductive health knowledge and premarital sexual attitudes in students at SMK Muhammadiyah 1 Rangkasbitung, Lebak Regency. Methods: Cross-sectional through a point time approach where samples were taken using a total sampling of 97 respondents. Data analysis using chi square test. Results: Demonstrate the level of reproductive health knowledge related to premarital sexual attitudes (p-value 0.023). Conclusion: There is a relationship between the level of knowledge of reproductive health and sexual attitudes. It is hoped that the school can provide information and socialization about the impact of free sex in an effort to minimize promiscuity, as well as educating how to positively respond to students’ attraction to the opposite sex so that the growth and development process can take place optimally.